Challenges Faced by Orphans at School In Busheyi district A case Study of Bugingi Sub County - Kinconco Pheonah (Kampala : Uganda Christian University Mukono, 2009)
Uganda Christian University Mukono BCDM
Includes References (p. 24)Appedixes (p.25-30)